2018
DOI: 10.1136/tobaccocontrol-2017-054053
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Income and Taxation in a Price-Tiered Cigarette Market: findings from the ITC Bangladesh Surveys

Abstract: background Taxing tobacco is among the most effective measures of tobacco control. However, in a tiered market structure where multiple tiers of taxes coexist, the anticipated impact of tobacco taxes on consumption is complex. This paper investigates changing smoking behaviour in lieu of changing prices and changing income. The objective of the paper is to evaluate the effectiveness of change in prices (through taxes) and change in income in a price-tiered cigarette market. Method A panel dataset from the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Pakistan has very complex tax system and different laws in its land as the proximities with Afghanistan border former Federally Administered Tribal Areas (FATA), Azad Jammu & Kashmir (AJK) territory and main-land where law enforcement has high variations, further aggravates the tobacco prevalence scenario and tobacco control performance. The poor performance despite the high proportion of excise tax in the lowest prices for cigarettes in the region are in conformity with the findings of other studies (Huq, Nargis, Lkhagvasuren, Hussain & Fong, 2018) which associate the success of tobacco control with the tax structure to control tier switching. Though taxation has been one of the most important and favorite intervention for the governments to control tobacco prevalence as well as raise revenue for different functions of the government.…”
Section: Discussionsupporting
confidence: 89%
“…Pakistan has very complex tax system and different laws in its land as the proximities with Afghanistan border former Federally Administered Tribal Areas (FATA), Azad Jammu & Kashmir (AJK) territory and main-land where law enforcement has high variations, further aggravates the tobacco prevalence scenario and tobacco control performance. The poor performance despite the high proportion of excise tax in the lowest prices for cigarettes in the region are in conformity with the findings of other studies (Huq, Nargis, Lkhagvasuren, Hussain & Fong, 2018) which associate the success of tobacco control with the tax structure to control tier switching. Though taxation has been one of the most important and favorite intervention for the governments to control tobacco prevalence as well as raise revenue for different functions of the government.…”
Section: Discussionsupporting
confidence: 89%
“…One study each from Thailand 45 , Sri Lanka 46 , Indonesia 47 , and Myanmar 48 , reported positive or no association between price and consumption of tobacco products. In Bangladesh, two studies reported a positive 49 , 50 association between price/tax of tobacco products with their consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The cross price elasticity often helps in indicating a shift in consumption to substitutes/ complementary products. Besides directly stating the cross price elasticity of tobacco products, few studies also linked the increase in the price of one tobacco product to the shift of tobacco consumers to other tobacco products or brands 46 , 50 . We, however, do not describe the findings of product shifting/substitution in detail in this study, and limit ourselves to reporting clear findings of cross price elasticity only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangladesh has a tiered tax system, with four tiers, in which low-priced cigarettes are taxed at a substantially lower rate than medium-priced and high-priced cigarettes. Huq et al find that, between 2009 and 2011/2012, the share of the lowest price segment has increased by more than 12 percentage points, as smokers have down-traded in response to higher prices 9. The different price tiers give smokers more flexibility of choice when faced with income shocks.…”
Section: Tax Structure Differential Prices and Substitution Possibilmentioning
confidence: 99%